The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008 10th Anniversary International Conference on Transparent Optical Networks 2008
DOI: 10.1109/icton.2008.4598408
|View full text |Cite
|
Sign up to set email alerts
|

Doped fiber lasers: From telecom to industrial applications

Abstract: Erbium and ytterbium doped fiber lasers are becoming important sources from telecom to industrial applications. This work focuses on laser architectures for non-conventional telecommunication bands and high power pulsed sources for micromachining and material processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Therefore, fiber lasers that can generate picosecond or even femtosecond pulses at a lower cost are more favorable to researchers. [ 151 ]…”
Section: Application Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fiber lasers that can generate picosecond or even femtosecond pulses at a lower cost are more favorable to researchers. [ 151 ]…”
Section: Application Prospectsmentioning
confidence: 99%
“…There- fore, fiber lasers that can generate picosecond or even femtosecond pulses at a lower cost are more favorable to researchers. [151] Chiodo et al used a Yb-doped fiber laser to ablate AA6082-T4 alloy and explored the properties of pulsed fiber lasers for ablating materials. They found that laser ablation increased the shear strength by 20%, as compared with traditional methods.…”
Section: Materials Processingmentioning
confidence: 99%
“…The vast experience in the context of optical communication systems has influenced positively in the development of high power fiber lasers, speeding up their progress [1][2][3][4]. This kind of lasers is able to cover a wide range of applications: medical, monitoring and remote sensing, laser radar, space communications, materials processing and defence, among others [5]. However, high power lasers require some specific characteristics of the laser source, such as high beam quality and efficiency, which often are not straightforward to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…The master oscillator is a single-mode laser that is the seed laser of the power amplifier. The most significant advantage, in addition to its complete modular architecture, is that the generation of the pulse is totally independent of the optical amplification process because the characteristics of the modulation signal can be controlled electronically [5]. This capability is pivotal in some applications, such as materials processing, where pulses with duration of the order of nano or pico seconds are required.…”
Section: Introductionmentioning
confidence: 99%